Technological and Nutritional Challenges, and Novelty in Gluten-Free Breadmaking - a Review - Paola Conte; Costantino Fadda; Natalia Drabińska; Urszula Krupa-Kozak (Polish Journal of Food and Nutrition Sciences)
The presence of gluten is considered fundamental for successful breadmaking. However, the ingestion of gluten by susceptible individuals has been associated with the development of gluten-related disorders such as celiac disease, wheat allergy, and non-celiac gluten sensitivity. The elimination of gluten from cereal-based baked products has a detrimental effect on the breadmaking process and sensory properties, and raises technological challenges in terms of making good quality leavened bread. The use of non-gluten raw materials changes the rheological behaviour of the gluten-free dough, which may result in different processing performance and associated post-baking quality of the obtained bread. Gluten-free bread tends to have a poor visual texture characteristics, a low nutritional value, reduced mouthfeel and flavour, as well as a shorter shelf-life. The aim of this review is to present the main problems related to gluten-free breadmaking technology and to summarise recent findings in the improvement of the technological, nutritional, and sensory properties of gluten-free bread. A great deal of this review focuses on the development of novel and healthy gluten-free breads formulated with flours, starches, hydrocolloids, and alternative nutrient-dense raw materials, which should fulfil all quality requirements for bakery products as well as meet the needs of celiac consumers.